2022
DOI: 10.1108/f-02-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved indoor environment on recovery from COVID-19 infections: a review of literature

Abstract: Purpose This study aims to explore the impact of the indoor environment on recovery from COVID-19 infections. Extant literature on the impact of the four key themes of the indoor environment (indoor air quality, indoor thermal quality, daylighting and visual comfort, and acoustic comfort) on COVID-19 infection and recovery rates were reviewed. Design/methodology/approach Data collection for this study was based on extant literature within the Scopus database and scoped to a time frame of 2020–2021 because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Several studies on hospital design and respiratory disease prevention have revealed important factors that can prevent the spread of COVID-19. A study by Afful et al (2022) found that proper ventilation and the use of air purifiers can improve indoor air quality and decrease the spread of COVID-19. Furthermore, Fleming et al (2023) and the CDCP (2021) suggested that the implementation of heating, ventilation and air conditioning (HVAC) systems with outdoor air dampers can improve indoor air quality and prevent the spread of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies on hospital design and respiratory disease prevention have revealed important factors that can prevent the spread of COVID-19. A study by Afful et al (2022) found that proper ventilation and the use of air purifiers can improve indoor air quality and decrease the spread of COVID-19. Furthermore, Fleming et al (2023) and the CDCP (2021) suggested that the implementation of heating, ventilation and air conditioning (HVAC) systems with outdoor air dampers can improve indoor air quality and prevent the spread of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the pandemic, measures were introduced for on-site workers to contain infection risks [ 41 ] and to safeguard their health and wellbeing [ 42 ]. Behavioural rules were adopted: e.g., social distancing, disinfecting of hands and contact points, and ventilating with fresh air [ 43 45 ]. Social distancing was furthered using one-way traffic signage, spatial-numerical occupant limitation, and an increase of building access points [ 46 ].…”
Section: Introductionmentioning
confidence: 99%